2005
DOI: 10.1021/la047440e
|View full text |Cite
|
Sign up to set email alerts
|

Au Nanoparticles and Polyaniline Coated Resin Beads for Simultaneous Catalytic Oxidation of Glucose and Colorimetric Detection of the Product

Abstract: In this letter, we report the synthesis of Au nanoparticles (NPs) and polyaniline (PANI) on the same cation-exchange resin beads and demonstrate their use in catalyzing the oxidation of glucose to gluconic acid by Au NPs and simultaneously in detecting the formation of the acid by the color change of PANI. The synthesis was carried out by exchanging the cations of the resins with HAuCl4 and anilinuium chloride and then reducing the metal ions by NaBH4 to produce Au NPs followed by polymerization of aniline usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…This figure shows a peak at 540 nm which is indicative of the formation of gold nanoparticles in the colloidal solution; this is in agreement with the results described in the literature [14,16,17].…”
Section: Preparation Of the Colloidal Gold Solutionssupporting
confidence: 92%
See 1 more Smart Citation
“…This figure shows a peak at 540 nm which is indicative of the formation of gold nanoparticles in the colloidal solution; this is in agreement with the results described in the literature [14,16,17].…”
Section: Preparation Of the Colloidal Gold Solutionssupporting
confidence: 92%
“…Various reports have described the preparation of nanoparticlesbased electrodes for diverse applications [14][15][16]. The electrocatalytic oxidation of carbohydrates on this type of electrode is attractive because of interest in sugaroxygen fuel cell application, as well as sugar sensors for the medical and food industry [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of PANI/TiO 2 , PANI/Cu, PANI/Au, PANI/Ag has been reported. [9][10][11][12][13][14][15][16][17][18] Conducting PANI supported PdNPs were synthesized by the reduction of Pd nitrate on the surface of PANI through electrochemical methods. [19] Amaya et al [20] reported on the template synthesis of CP/PdNPs composites.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocomposites are not only known for their nano-dimension but also for exhibiting synergistic properties due to the combination of its two different components, i.e. matrix and filler, in particular, conducting polymer and metal-based nanocomposites formed by decorating a conducting polymer with metal nanoparticles such as Ag, Au, Pt or Pd (Hable and Wrighton 1991;Majumdar et al 2005Majumdar et al , 2006Tseng et al 2005) have been reported for multiple technological application related to catalysis, sensors, electronic devices like transistor, etc. In general, there are two suitable methods of synthesis of conducting polymer metal-based nanocomposite.…”
Section: Introductionmentioning
confidence: 99%